Progressing Beyond the Standard Model - B. A. Robson (Advances in High Energy Physics)
The Standard Model has enjoyed considerable success in describing a whole range of phenomena in particle physics. However, the model is considered incomplete because it provides little understanding of other empirical observations such as, the existence of three generations of leptons and quarks, which apart from mass have similar properties. This paper examines in some detail the basic assumptions upon which the Standard Model is built and compares these with the assumptions of an alternative model, the Generation Model. The Generation Model provides agreement with the Standard Model for those phenomena which the Standard Model is able to describe, but it is shown that the assumptions inherent in the Generation Model allow progress beyond the Standard Model.